2021
DOI: 10.1007/s10856-021-06536-4
|View full text |Cite
|
Sign up to set email alerts
|

Microfibrillated cellulose films containing chitosan and tannic acid for wound healing applications

Abstract: The effectiveness of tannic acid as antimicrobial and wound healing for burns have been shown for a century; however, uncontrolled target dosage may result in undesirable side-effects. Remarkably, tannic acid polyphenols compounds crosslinked with polymeric materials produce a strong composite containing the beneficial properties of this tannin. However, investigation of the crosslink structure and its antibacterial and regenerative properties are still unknown when using nanocellulose by mechanical defibrilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Meanwhile, the ether bond (2) was formed as a result of interaction between the hydroxyl group of Cs and TA, respectively, which was proven by the reduction in C O C peak intensity at 1065-1022 cm À1 . This was line with a study reported by Aliabadi et al 44 who found a large alteration at the 1737-1671 cm À1 and 1043-1030 cm À1 regions, when TA was incorporated into the microfibrillated cellulose/Cs films.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 93%
“…Meanwhile, the ether bond (2) was formed as a result of interaction between the hydroxyl group of Cs and TA, respectively, which was proven by the reduction in C O C peak intensity at 1065-1022 cm À1 . This was line with a study reported by Aliabadi et al 44 who found a large alteration at the 1737-1671 cm À1 and 1043-1030 cm À1 regions, when TA was incorporated into the microfibrillated cellulose/Cs films.…”
Section: Fourier Transform Infrared Spectroscopysupporting
confidence: 93%
“…25 Moreover, TA showed good antibacterial ability and strong bactericidal effect against Staphylococcus aureus and Escherichia coli. 28,29 Meanwhile, TA can inhibit the production of NO by stimulated macrophages and exhibits good anti-inflammatory activity. 30 In this study, we chose a hydrogel system of agar and polyvinyl alcohol (PVA).…”
Section: Introductionmentioning
confidence: 99%
“…The MFC load is reduced when a plasticizer is added. This reduces the mechanical reinforcement, a behavior observed in previous MFC and polyols antibacterial films (Liu et al 2013;Aliabadi et al 2021). Opposite results (an increase in the TI) were obtained for cellulose nanocrystals (CNC) with the addition of mannitol, sorbitol, and glycerol.…”
Section: Physical-mechanical Properties For Filmsmentioning
confidence: 85%